The Effect of Concentration and Time Interval of Golden Snail Liquid Organic Fertilizer on The Growth and Yield of Sweet Corn (Zea mays var.saccharata Sturt) - Zahanis, Zahanis; Putri, Cindy Agustin; Ernita, Milda; Afrironadiyanti (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
This research aims to obtain the correct concentration and time interval for administering golden snail Liquid Organic Fertilizer (LOF) on the growth and yield of sweet corn ( Zea mays var. saccharata Sturt). The experiment was carried out in Korong Gadang Village, Padang, West Sumatra on Ultisol soil type with a height of 10 meters above sea level. The experiment used a factorial completely randomized design (CRD), the first factor was the LOF of golden snails 0ml/L, 50 ml/L, 100 ml/L, the second factor was the time interval for administering 5, 10, and 15 days with 3repetitions. times to obtain 27 experimental units. The parameters observed consisted of plant height, ILD, age at which male flowers appeared, age at which female flowers appeared, weight of cobs with husks, weight of cobs without husks, length of cobs, number of rows of cobs, number of seeds per row, weight of fresh shells, production per plot and per Ha. The experimental results showed that there was an interaction between the concentration and the time interval for administering golden snail LOF on the weight of shelled cobs and the weight of fresh shelled shells when given aconcentrationof100ml/L.